Recent Advances in Biodiesel Production: Ultrasound-Assisted Interesterification of Palm Oil with Methyl Acetate - Ansori, Ansori; Syafaatullah, Achmad Qodim; Variyana, Yeni; Mahfud, Mahfud (ASEAN Journal of Chemical Engineering, 2025)
Currently, fossil fuels (non-renewable) are used continuously to meet bioenergy needs. Every year, there is an increase in bioenergy consumption, which will eventually lead to the depletion of fuel reserves. Therefore, it is necessary to have alternative and renewable fuels to substitute for the use of fossil fuels. One such application is the production of biodiesel, which serves as a substitute for diesel fuel. Biodiesel is made via the transesterification of triglycerides and methanol, with glycerol as a byproduct. The formation of glycerol holds no economic value and is deemed waste in biodiesel production, necessitating a separation process. Therefore, this research proposes an innovative method, specifically the non-alcoholic or interesterification reaction pathway, which involves three consecutive reversible reactions. In this reaction, methyl acetate is used to replace methanol, resulting in the production of triacetin instead of glycerol, which is completely soluble in biodiesel and offers a greater additional value than glycerol. To enhance the reaction rate and yield, potassium methoxide catalyst and ultrasound were used in this research. Meanwhile, to evaluate the influence of significant operational parameters on the interesterification reaction, experiments were carried out on different operating factors, namely a methyl acetate to oil molar ratio (3:1 to 25:1), reaction temperature (35 to 65 oC), catalysts (0.5 to 2% (w/w)), and interesterification time (1 to 30 minutes). It has been observed that the optimal yield is achieved at a 15:1 molar ratio, with a 1% catalyst amount, a reaction temperature of approximately 55 oC, and a reaction time of 5 minutes, resulting in a yield of 81.26%. Furthermore, a kinetic study was conducted to determine the activation of energy and rate constantly suitable for the second-order approximation. The reaction rate constant is 0.287 L/(mol.min) at an operational temperature of 55 oC, and the resulting activation energy is 50.50 kJ/mol.